2022
DOI: 10.3390/cancers14164032
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Targeting as a New Strategy to Decrease Glioblastoma Aggressiveness

Abstract: Glioblastoma is the most commonly malignant and aggressive brain tumor, with a high mortality rate. The role of the purine nucleotide adenosine and its interaction with its four subtypes receptors coupled to the different G proteins, A1, A2A, A2B, and A3, and its different physiological functions in different systems and organs, depending on the active receptor subtype, has been studied for years. Recently, several works have defined extracellular adenosine as a tumoral protector because of its accumulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…Preclinical studies also support the continued investigation of adenosine signaling blockade in GBM therapy ( Jin et al 2021 ; Bova et al 2022 ). Inhibition of the adenosine receptor A 2B R, which is highly up-regulated on GBM cells ( Fig.…”
Section: Relieving the Immune-suppressive Metabolic Environment In Gbmmentioning
confidence: 86%
“…Preclinical studies also support the continued investigation of adenosine signaling blockade in GBM therapy ( Jin et al 2021 ; Bova et al 2022 ). Inhibition of the adenosine receptor A 2B R, which is highly up-regulated on GBM cells ( Fig.…”
Section: Relieving the Immune-suppressive Metabolic Environment In Gbmmentioning
confidence: 86%
“…Additionally, adenosine can stimulate the accumulation of MDSCs within TME and promote MDSCs expansion ( 172 ). Moreover, activation of A2AR on neutrophils, M1 macrophages, NK cells, Th1 cells and DCs inhibited antitumor cytokines and chemokines production ( 173 ). Finally, the adenosine stimulated cancer cells result in enhanced proliferation, migration and metastasis in enhanced proliferation, migration and metastasis ( 174 ).…”
Section: Oncogenic Mechanisms Leading To Immune Evasion and Possibili...mentioning
confidence: 99%
“…Adenosine and its receptors have multiple roles in the brain, including activation of microglia/macrophages and neurons, regulation of the immune response, and modulation of neurotransmitter release and neuronal plasticity. In brain tumors, increased levels of adenosinecreated by the tumor microenvironment, e.g., hypoxiaare thought to inhibit T cells leading to immune response evasion; the effect of adenosine on tumor cell proliferation (through the MAPK signaling pathway) has been more controversial, with equal reports on anti-tumor effects (140). 18 F-CPFPX is a specific ligand for the adenosine receptor A1AR (Figure 7) and in one preliminary study showed uptake restricted to the peritumoral tissue, suggesting a possible cellular reaction of this tissue to infiltrating tumor cells; however, T/N ratios were low and the at that time ambivalent role of adenosine receptors likely precluded further investigations (141).…”
Section: Adenosine-based (Receptor-targeting) Agentsmentioning
confidence: 99%